Cover Feature: Photoelectrochemical Complete Decomposition of Cellulose for Electric Power Generation (6/2021). Issue 6 (25th February 2021) - Kageshima, Yosuke; Yoshimura, Takumi; Koh, Sangho; Mizuno, Masahiro; Teshima, Katsuya; Nishikiori, Hiromasa
Abstract : The Cover Feature represents electric power generation in harmony with nature by photoelectrochemically decomposing cellulose, which accounts for a major portion of waste biomass, as a direct fuel. In their Full Paper, Y. Kageshima et al. demonstrate that a photo‐assisted fuel cell (photofuel cell; PFC) consisting of a porous TiO2 photoanode coated with a regenerated cellulose thin film and Pt‐deposited Ni foam cathode exhibits excellent photovoltaic performances ( i.e ., 1.1 V of open‐circuit voltage and quantum efficiency up to 52% in the ultraviolet region). The product analyses show that cellulose can be photoelectrochemically decomposed into CO2 completely through short carboxyl acids, such as gluconic acid, oxalic acid, acetic acid, and formic acid. The present PFC represent a potential means of converting almost all the Gibbs free energy of waste biomass into electric power with the assistance of photon energy.More information can be found in the Full Paper by Y. Kageshima et al .